2003
DOI: 10.1103/physreve.68.026410
|View full text |Cite
|
Sign up to set email alerts
|

3/2 harmonic generation by femtosecond laser pulses in steep-gradient plasmas

Abstract: The onset of an electron parametric instability and 3/2 harmonic generation in variable-scale-length plasmas on solid surfaces using femtosecond pulses is observed. With the intensity approaching 10(18) W/cm(2), the instability threshold is already reached at plasma scale lengths of the order of the laser wavelength. A well-collimated harmonic emission with unusually broad spectrum is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…With this intensity, a much shorter density scale length was enough for observing three-halves harmonic emission. Similar results were previously achieved by Tarasevitch et al, 23 who observed 3x/2 emission at extremely short plasma scale lengths (L % k 0 ) for a peak intensity of 7Á10 17 W/cm 2 . In this case, the excited plasma waves had a very broad spectrum and the 3x/2 emission was highly collimated.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…With this intensity, a much shorter density scale length was enough for observing three-halves harmonic emission. Similar results were previously achieved by Tarasevitch et al, 23 who observed 3x/2 emission at extremely short plasma scale lengths (L % k 0 ) for a peak intensity of 7Á10 17 W/cm 2 . In this case, the excited plasma waves had a very broad spectrum and the 3x/2 emission was highly collimated.…”
Section: Introductionsupporting
confidence: 91%
“…A distinctive feature of these studies was the directionality of the X-ray emission, which was found to be strictly correlated to the directionality of the 3x/2 emission. 22,23 The latter was proven to be maximum in the plane of incidence for P-polarization and in the perpendicular plane for S-polarization. 12,22 Non-isotropic distribution of the X-ray yield was further investigated by different authors.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The 3/2ω radiation is generated as a result of stimulated Raman scattering by one of these plasmons. The instability threshold is determined by the density scale length [7]. On the other hand, the 2ω radiation is produced by electron plasma wave coupling at the critical density surface of the plasma.…”
Section: Introductionmentioning
confidence: 99%